Theoretical problems of the methodology of balance assessment of the cycle of macroelements in the “fertilizer-soil-plant” system - Khristenko, A.O. (AgroChemistry and Soil Science, 2020)
The strategy of activities aimed at achieving a deficit-free balance of nutrients in agriculture requires improvement, theoretical justification and determination of economic feasibility. The aim of the research is to improve the theoretical aspects of the balance assessment of the cycle of macroelements in the soil-plant system. The task was to identify new patterns of formation of the balance of nitrogen, phosphorus and potassium in the soil-plant system and to develop basic models of economically justified level of balance of nutrients. Applied materials and methods: results of long-term research in stationary field experiment; analysis, generalization and statistical data processing of stock and modern literature materials (partially combined in an electronic database); analysis and generalization of data of the agrochemical service of the country. Researched objects: main soils of Ukraine (object of direct research- typical heavy loam chernozem); models of economically justified level of balance of nutrients in the soil-plant system. It is found that with the systematic application of fertilizers (even under the conditions of a negative balance of nutrients) the content of mobile compounds of nitrogen, phosphorus and potassium in the soil tends to increase. This led the author to suggest that the idea of a significant deterioration of the trophic state of soils in a negative balance of nutrients is not theoretically sound and somewhat exaggerated. In this regard, the author recommends approaching the interpretation of the results of balance calculations with some caution. Mathematical models are developed and standards for the dynamics of phosphorus content in the soils of Ukraine depending on the rate of fertilizers and the duration of their application are calculated. It is established and theoretically substantiated that with systematic application of even small doses of fertilizers, simple reproduction of soil fertility is achieved automatically. A basic model of economically justified level of nutrient balance for extended reproduction of soil fertility is proposed. The parameters of the model may vary depending on climatic conditions, fertilizer prices, the set of crops grown and the level of agricultural culture.